STRATEGI PEMASARAN DIGITAL AKUN @ANNASHSHALIHCERDAS DALAM MENGKOMUNIKASIKAN NILAI PENDIDIKAN ISLAM - Prasetyo Adinugroho (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
Islamic education in Indonesia is undergoing a significant transformation in the digital era of the 21st century, with Integrated Islamic Schools (SIT) increasingly in demand as a solution to concerns about moral degradation, violence, and urban hedonism. This trend demands that Islamic educational institutions effectively communicate their core values to urban society. This study aims to analyze the digital marketing strategy implemented by Annash Shalih Cerdas School in communicating Islamic educational values through the Instagram platform (@annashshalihcerdas). Using a descriptive qualitative approach and case study method, this research examines the Instagram account content during the 2024-2025 period. Data analysis was conducted using thematic content analysis techniques based on the 7P Marketing Mix framework (Product, Price, Place, Promotion, People, Process, Physical Evidence). The results show that Annash Shalih Cerdas successfully integrates all seven marketing elements to frame and convey its core narrative of "Pious & Intelligent". This strategy functions not only as promotion but has evolved into digital branding that builds community, trust, and value differentiation amid the competition among urban Islamic schools. The findings of this study provide practical contributions as a model of digital communication strategy for other Islamic educational institutions in adapting to the dynamics of 21st-century education and aspiring towards global standards.